A Call for Compassion in Social Media Studies - Deuze, Mark (Social Media + Society, 2015)
In social media we can see ourselves live, as much as we are blind to media. Compassion is therefore key in studying the role of social media in everyday life.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMDU2MzA1MTE1NTgwMzMz